Parkett : The Parkett series with contemporary artists (Zürich : Parkett-Verlag, 1993)
Table of Content : Trickster Eva Hesse by Ursula Panhans-Bühler ; Clockwork (Jon Kessler) by Douglas Blau ; Stephan Balkenhol : Stephan Balkenhol, The Figure as Witness by Neal Benezera As Time goes by by Vik Muniz Autonomous ; People by Max Katz 57 Penguins by Jean-Christophe Ammann ; Sophie Calle : Sophie Calle’s Uncertainty Principle by Luc Sante ; Postcards to Sophie Calle by Joseph Grigely ; The Hpyerfiction of Life and Death by Patrick Frey ; Sophie Calle’s and Gregory Shepard’s Double Blind by Robert Beck ; Richmond Burton, Insert Dimensions Variable: Liz Larner by Robert Beck ; Rudolf Schwarzkogler by László Földényi Berlin – Fast Forward, Cumulus from Europe by Christoph Tannert ; Nobody Wants to See a Movie with Madonna in It, Cumulus from America by David Rimanelli ; The Applied Art of Animal Breeding by Alexander Popper
Mondrian sighted in front of Matisse at MOMA As if it had suddenly stepped off the wall of the museum, a Mondrian—in the form of a coat worn by a woman—strolls through the Matisse exhibition at MOMA (the classic art event of the past winter): Thus does Mondrian steal his way into the show of his colleague. We are reminded of Sophie Calle’s GHOSTS (1991/92), appearing in the same museum at the exhibition DisLocations. The artist asked the entire museum staff—from director to guards and cleaners—for descriptions of paintings that she had removed from the walls. Through the commentaries thus garnered, she professed her interest in personal connotations, in recollection and perception on the opposite shore of art history. Both Sophie Calle and Stephan Balkenhol—our collaborating artists in this issue—develop their works as if to bring the outside world into art through the emphatic yet impassive involvement of other human beings. However one might say that the focus of Calle’s interest is actually that terrain which Balkenhol assiduously avoids. (editorial by publisher)
boek
Keywords: Balkenhol, Stephan; Calle, Sophie